Disseminated Cutaneous Mycobacterium chelonae Infection in a Patient With Acute Myeloid Leukemia. (26th November 2014) - Roukens, Anna Helena; Mendels, Elodie J.; Verbeet, Nicolette L.; von dem Borne, Peter A.; Nicolae-Cristea, Alina R.; Bentvelsen, Robbert G.; van Doorn, Remco; de Boer, Mark G.
Abstract: We report a case of disseminated cutaneous Mycobacterium chelonae infection in a patient who was treated with chemotherapy for acute myeloid leukemia. We discuss the clinical manifestations, diagnosis, and treatment of this unusual infection in neutropenic patients.